2009
DOI: 10.1002/art.24432
|View full text |Cite
|
Sign up to set email alerts
|

Effector CD8+ T cells in systemic sclerosis patients produce abnormally high levels of interleukin‐13 associated with increased skin fibrosis

Abstract: Objective. T lymphocytes play an important role in systemic sclerosis (SSc), a connective tissue disease characterized by inflammation, fibrosis, and vascular damage. While their precise role and antigen specificity are unclear, T cell-derived cytokines likely contribute to the induction of fibrosis. The aim of this study was to establish the role of cytokine dysregulation by T cells in the pathogenesis of SSc.Methods. To identify relationships between a specific cytokine, T cell subset, and the disease course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 43 publications
4
97
0
1
Order By: Relevance
“…The disease duration was calculated from the time of onset of the first non-Raynaud phenomenon. Skin sclerosis was evaluated with the modified Rodnan skin thickness score (MRSS) (19) and graded as mild (MRSS, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] or moderateto-severe (MRSS, 15-39) (20). SSc-related interstitial lung disease (ILD) was classified as extensive or limited disease based on combined evaluation with chest high-resolution computed tomography (HRCT) and pulmonary functional tests (21).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease duration was calculated from the time of onset of the first non-Raynaud phenomenon. Skin sclerosis was evaluated with the modified Rodnan skin thickness score (MRSS) (19) and graded as mild (MRSS, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] or moderateto-severe (MRSS, 15-39) (20). SSc-related interstitial lung disease (ILD) was classified as extensive or limited disease based on combined evaluation with chest high-resolution computed tomography (HRCT) and pulmonary functional tests (21).…”
Section: Patientsmentioning
confidence: 99%
“…These findings indicate that effector or memory CD8 + T cells, or both, are involved in SSc pathogenesis. Recent reports have shown that effector CD8 + T cells were directly involved in modulating dermal fibrosis in SSc via dysregulated IL-13 production (6,12). Memory T cells contain two populations of central memory and effector memory cells characterized by distinct homing potentials and effector functions (13).…”
mentioning
confidence: 99%
“…IL-13 plays a critical role in pathologic processes such as asthma, 20 fibrosis, 21,22 and cancer. 21,23 Several studies implicate IL-13 as an autocrine factor for several tumors that express IL-13Ra1, the signaling receptor for IL-13, 24 including Hodgkin lymphoma, 25,26 B-CLL, 27 and breast carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…There was a dysregulation in IL-13 production by effector CD8+ T-cells in SSc, not present in the healthy control group or in rheumatoid arthritis patients (p < 0.001). This dysregulated IL-13 production also correlated with the extent of skin fibrosis, with dcSSc showing higher levels of IL-13 compared with lcSSc (p < 0.01) [33].…”
Section: Interleukin-13mentioning
confidence: 82%